Identification of cognitive predictors of remission in depression following limited effect of repetitive transcranial magnetic stimulation on hot and cold cognitive systems - Derakhshan, Dorsa; Lipsman, Nir; Feinstein, Anthony; Levitt, Anthony; Eizenman, Moshe; Rabin, Jennifer; Giacobbe, Peter (Frontiers in Human Neuroscience, 2025)
IntroductionCognitive dysfunction is a chronic and debilitating element of major depressive disorder (MDD), which manifests as abnormal processing in hot (emotion-laden) and cold (emotion-independent) cognitive systems. Although the antidepressant properties of repetitive transcranial magnetic stimulation (rTMS) are well-established, its impact on hot and cold cognition requires further elucidation.MethodsProspective study of patients with MDD undergoing an acute course of high frequency rTMS to the left dorsolateral prefrontal cortex (L-DLPFC). MDD patients (N = 24) received a 4-to-6-week course of rTMS during which they were evaluated for depressive symptoms and completed cognitive assessments. Age-, sex-, and education-matched healthy controls (N = 33) also completed the cognitive tasks at the same intervals as the MDD patients.ResultsSustained antidepressant effect was observed following rTMS in MDD patients. Hot and cold cognition remained unaltered over the course of treatment. A pre-treatment baseline cognitive phenotype of those who achieve remission of their depressive symptoms with rTMS was identified, characterized by greater sustained attention, speed in correct identification of facial expressions, and free recall of words.ConclusionOur findings further validate the cognitive safety and clinical efficacy of rTMS as an intervention for MDD. Future research is required to further characterize the utility of pre-rTMS cognitive phenotyping in identified remitters, to aid in patient selection and treatment prognostication.